Pengaruh Store Atmosphere dan Service Quality Terhadap Revisit Intention - Limbong, Kasih Oktavia; Meutia, Riza Fanny (Economics, Business and Management Science Journal, 2025)
This study aims to analyze the influence of Store Atmosphere and Service Quality on Revisit Intention of visitors to Medan City Culinary Pajus. Competition in the culinary industry is increasingly fierce, requiring managers to understand the factors that can increase visitor loyalty through the intention to return. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to 120 respondents who were visitors to the Medan City Culinary Pajus. The data analysis technique used is multiple linear regression analysis to determine the simultaneous and partial influence. The analysis techniques used in this study are multiple linear regression, partial test (t-test), simultaneous signification test (F test), and determination coefficient. This can be seen from the significant value (0.047) of 0.05 and t-count (2.012) compared to t-table (1.986). The Service Quality variable has a significant effect on Revisit Intention. This can be seen from the significant value (0.000) 0.05 and t-count (5.021) compared to the t-table (1.986).